2022
DOI: 10.1063/5.0111792
|View full text |Cite
|
Sign up to set email alerts
|

Buffer gas cooled ice chemistry. I. Buffer gas cell and mm-wave spectrometer

Abstract: A new instrument is described that will employ buffer gas cooling with mm-wave rotational spectroscopy (60-90 GHz) to probe molecules desorbed from astrochemical ices prepared in an ultrahigh vacuum environment. Here the design and performance of the buffer gas cell, mm- wave spectrometer and data acquisition system are reported, while application to molecules desorbed from ice surfaces will be described in a future publication. The effective temperature of the neon-cooled buffer gas cell is determined by moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Following ∼9 collisions with cold Ne atoms in the BGC, the desorbed species are cooled and detected with broadband millimeter-wave radiation . A schematic of the 60–90 GHz spectrometer is given in Figure , and a detailed description of the CPICE data acquisition system is provided in ref . The fast on-board averaging at 10 GS/s in CPICE lends itself well to TPD measurements given that a finite number of molecules are present within the ice sample in each experiment and desorb within a narrow temperature window.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following ∼9 collisions with cold Ne atoms in the BGC, the desorbed species are cooled and detected with broadband millimeter-wave radiation . A schematic of the 60–90 GHz spectrometer is given in Figure , and a detailed description of the CPICE data acquisition system is provided in ref . The fast on-board averaging at 10 GS/s in CPICE lends itself well to TPD measurements given that a finite number of molecules are present within the ice sample in each experiment and desorb within a narrow temperature window.…”
mentioning
confidence: 99%
“…In addition to condensed-phase studies, CPICE is also equipped to probe gas-phase molecules which are initially at room temperature and directly injected into the BGC . This permits a comparison of the gas-phase abundances observed with those measured following sublimation off an ice surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37 In previous work, we showed the successful application of this technique for the gas-phase injection of n-PrCN, where we examined anti-n-PrCN and gauche-n-PrCN to determine the rotational temperature of molecules within a 25 K cell. 38 In our most recent work with normal-and iso-propanol (PrOH), we applied CPICE to study molecules desorbing from an ice surface over the course of temperature-programmed desorption (TPD). 36 This previous work revealed surprising conformer-specific desorption profiles and quantified the relative abundances of conformers and isomers following both room-temperature gas-phase injection and separately following TPD of PrOH ices generated at 4 K. The results showed that the relative conformer yield varied dramatically during desorption, likely reflecting the composition of the ice itself.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While cold, these molecules are subjected to broadband excitation pulses resulting in the detection of highly resolved molecular signals via rotational transitions immediately following desorption . In previous work, we showed the successful application of this technique for the gas-phase injection of n -PrCN, where we examined anti-n -PrCN and gauche - n -PrCN to determine the rotational temperature of molecules within a 25 K cell . In our most recent work with normal - and iso -propanol (PrOH), we applied CPICE to study molecules desorbing from an ice surface over the course of temperature-programmed desorption (TPD) .…”
Section: Introductionmentioning
confidence: 99%